Spontaneous pneumothorax in pregnancy: a case report and literature review - TAMATEY, A.A; ADOMAKO, K.A.; LARBI, G.O.; OKYERE, I; NTUMY, M.Y. (HSI Journal (2023) Volume 4 (Issue 1):481-484. https://doi.org/10.46829/hsijournal.2023.6.4.1.481-484, 2023)
Spontaneous pneumothorax occurring in pregnancy is a rare condition that can be life-threatening if not recognized and treated on time. We present a 38-year-old primigravida at 34 weeks gestational age who presented with a 2-week history of progressive dyspnoea. Clinical assessment was consistent with a right pneumothorax which was confirmed by a chest x-ray. She was managed with a right chest tube insertion. She later had an elective cesarean delivery. Six months later, both mother and baby were fine. The clinical significance of this article is that pneumothorax in pregnancy may mimic some complications of pregnancy itself and may thus be missed if the clinician does not have pneumothorax also in mind.
Research Article
Keywords: Spontaneous pneumothorax; pregnancy; dyspnoea; clinical significance; Ghana